BmILF and i-motif structure are involved in transcriptional regulation of BmPOUM2 in Bombyx mori. Issue 4 (29th November 2017) - Niu, Kangkang; Zhang, Xiaojuan; Deng, Huimin; Wu, Feng; Ren, Yandong; Xiang, Hui; Zheng, Sichun; Liu, Lin; Huang, Lihua; Zeng, Baojuan; Li, Sheng; Xia, Qingyou; et al.
Abstract: Guanine-rich and cytosine-rich DNA can form four-stranded DNA secondary structures called G-quadruplex (G4) and i-motif, respectively. These structures widely exist in genomes and play important roles in transcription, replication, translation and protection of telomeres. In this study, G4 and i-motif structures were identified in the promoter of the transcription factor gene BmPOUM2, which regulates the expression of the wing disc cuticle protein gene ( BmWCP4 ) during metamorphosis. Disruption of the i-motif structure by base mutation, anti-sense oligonucleotides (ASOs) or inhibitory ligands resulted in significant decrease in the activity of the BmPOUM2 promoter. A novel i-motif binding protein (BmILF) was identified by pull-down experiment. BmILF specifically bound to the i-motif and activated the transcription of BmPOUM2 . The promoter activity of BmPOUM2 was enhanced when BmILF was over-expressed and decreased when BmILF was knocked-down by RNA interference. This study for the first time demonstrated that BmILF and the i-motif structure participated in the regulation of gene transcription in insect metamorphosis and provides new insights into the molecular mechanism of the secondary structures in epigenetic regulation of gene transcription.